New Geoecoprotective Properties Of The Construction Materials For Underground Infrastructure Development. (2016) - Svatovskaya, Larisa; Sychov, Maxim; Sychova, Anastasia; Gravit, Marina
Abstract: The point of the paper is to introduce new characteristics of the underground construction materials which are important for geoecoprotection of infrastructure in the sense of durability and wastewater resistance. The main idea is using absorption ability of underground constructions on the cement base. It was shown that utilization of silica sol solution instead of water allows one to improve more than 50% main properties of the concrete on the cement base. Because of that the new technology of fabrication of the underground constructions on the cement base has been suggested (silica sol absorption technology, SAT - technology). Underground construction ability to absorb water has been investigated using wastewater with heavy metal ions. Such kind of water has been absorbed by construction and detoxication of wastewater was demonstrated due to formation of heavy metal ions silicates in pores and capillary of material.